Pinch Analysis for Sustainable Energy Planning Using Diverse Quality Measures - Tan, Raymond Girard R. (Animo Repository, 2013)
© 2013 Woodhead Publishing Limited All rights reserved.. This chapter presents the generalised Pinch principles for energy planning involving the optimal matching of sources and sinks (or demands) using diverse measures of energy quality such as Carbon Footprint, Agricultural-Land Footprint, Water Footprint, emergy and inoperability. These indices provide numerical measures of the quality of energy streams allocated between sources and sinks under different contexts. Nevertheless, there are common principles that apply to all such systems, which allow the use of a two-phase insight-based Pinch Analysis approach comprising targeting (benchmarking with first principle), followed by the determination of the optimal energy allocation network. Five different examples are solved here to illustrate the application of such Energy Planning Composite Curves (EPCC).